Unexpected Vulnerability of DPEphos to C−O Activation in the Presence of Nucleophilic Metal Hydrides. Issue 49 (28th July 2020) - Cybulski, Mateusz K.; Beattie, Nicholas A.; Macgregor, Stuart A.; Mahon, Mary F.; Whittlesey, Michael K.
Abstract: C−O bond activation of DPEphos occurs upon mild heating in the presence of [Ru(NHC)2 (PPh3 )2 H2 ] (NHC=N‐heterocyclic carbene) to form phosphinophenolate products. When NHC=IEt2 Me2, C−O activation is accompanied by C−N activation of an NHC ligand to yield a coordinated N ‐phosphino‐functionalised carbene. DFT calculations define a nucleophilic mechanism in which a hydride ligand attacks the aryl carbon of the DPEphos C−O bond. This is promoted by the strongly donating NHC ligands which render a trans dihydride intermediate featuring highly nucleophilic hydride ligands accessible. C−O bond activation also occurs upon heating cis ‐[Ru(DPEphos)2 H2 ]. DFT calculations suggest this reaction is promoted by the steric encumbrance associated with two bulky DPEphos ligands. Our observations that facile degradation of the DPEphos ligand via C−O bond activation is possible under relatively mild reaction conditions has potential ramifications for the use of this ligand in high‐temperature catalysis. Abstract : Hydride ligands : Under mild conditions (25→90 °C), [Ru(N‐heterocyclic carbene)2 (PPh3 )2 H2 ]/DPEphos or [Ru(DPEphos)2 H2 ] undergo C−O bond activation of this catalytically important diphosphine ligand by attack of the nucleophilic Ru−H ligands.